Air‐entrainment problem in self‐compacting concrete - Szwabowski, Janusz; Łaźniewska-Piekarczyk, Beata (Journal of Civil Engineering and Management, 2009)
According to the actual state of knowledge and in accordance with the PN‐EN 2006–1 norm, it is recommended to use air‐entrainment as a basic way of assuring frost‐resistance of concrete. In case of self‐compacting concrete (SCC), achieving adequate air‐entrainment is a problematic issue because of one of the side‐effects of the functioning of a new generation of superplasticizers, i.e. excessive air‐entrainment (considerably higher than 2%) in a self‐compacting concrete mix. Thus, in this situation, the dosage of an air‐entraining admixture has to be reduced. It was discovered that the cause of an air‐entrainment effect of superplasticizers is a decrease of the surface tension value of the liquid phase in paste. In the paper, the problem of air‐entrainment is discussed, formed as a result of the functioning of a superplasticizer on the characteristics both of concrete and a mixture, depending on the content. To verify the influence a superplasticizer and an air‐entraining admixture have on concrete porosity structure parameters, concrete samples were tested during 300 cycles of freezing and testing the porosity structure according to PN‐EN 480–11. The tests of the structure show that air pores, depending on the level of mix flowability, can be regular and similar in shape and size to pores formed as a result of air‐entrainment admixture action. According to the actual state of knowledge on concrete technology, concrete is frost‐resistant if the value of porosity structure parameter stays within precisely set limits. The results of concrete testing have shown that the parameters of porosity structure do not stay within the precisely set limits, but self‐compacting concrete gets frost‐resistance F300 according to PN‐88/B‐06250. Issues connected with this fact are the subject of this paper. Santrauka Laikoma, kad betono atsparumą šalčio poveikiui galima užtikrinti naudojant orą įsiurbiančius priedus. Savaime susitankinančio betono orą įsiurbiančių priedų taikymas ypač painus, nes šiuo atveju galima naudoti tik naujos kartos plastiklius, kurie pasižymi didesniu oro įsiurbimu – >2 %. Norint įvertinti superplastiklių ir orą įsiurbiančių priedų įtaką betono porėtosios struktūros parametrams, buvo ištirta betono bandinių po 300 šaldymo ciklų struktūra pagal PN-EN 480-11 normų reikalavimus. Tyrimų rezultatai parodė, kad nors porėtosios struktūros parametrai nevisiškai atitinka reikalavimus, savaime sutankėjantis betonas pagal PN-88/B-06250 reikalavimus yra F300 klasės. Būtent šis klausimas išsamiai nagrinėjamas straipsnyje. Reikšminiai žodžiai: atsparumas šalčiui, betono porėtoji struktūra, orą įsiurbiantys priedai, superplastikliai, savaime sutankėjantis betonas.